2012
DOI: 10.1177/0961203312446386
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and antiphospholipid syndrome

Abstract: Vitamin D (vitD) has been shown to have multiple immunomodulatory properties. Hypovitaminosis D has been described in many systemic autoimmune diseases. Antiphospholipid syndrome (APS), an autoimmune disease characterized by immunemediated thrombosis and pregnancy loss, is a peculiar model for studying vitD, since these patients do not usually have a full-blown autoimmune disease, nor do they have particular restrictions regarding sun exposure. We assessed 25-OH vitD levels in 115 APS and 128 normal healthy do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
38
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 18 publications
5
38
0
1
Order By: Relevance
“…This letter to the editor presented the results of research conducted by Brazilian investigators in the group of forty-six PAPS patients, younger than 60 years, in whom the VitD levels were assessed in the autumn, when it was expected to be highest. VitD deficiency was found in 11% and insufficiency in 74% of these PAPS patients, resembling the findings of Italian authors [88] which have reported the prevalence of VitD deficiency in 17% and insufficiency in 60% of PAPS patients. It is interesting that Brazilian authors have noticed that VitD insufficient PAPS patients tended to be more overweighed than those with adequate VitD level [87].…”
Section: Role Of Vitamin D In Antiphospholipid Syndromesupporting
confidence: 88%
See 2 more Smart Citations
“…This letter to the editor presented the results of research conducted by Brazilian investigators in the group of forty-six PAPS patients, younger than 60 years, in whom the VitD levels were assessed in the autumn, when it was expected to be highest. VitD deficiency was found in 11% and insufficiency in 74% of these PAPS patients, resembling the findings of Italian authors [88] which have reported the prevalence of VitD deficiency in 17% and insufficiency in 60% of PAPS patients. It is interesting that Brazilian authors have noticed that VitD insufficient PAPS patients tended to be more overweighed than those with adequate VitD level [87].…”
Section: Role Of Vitamin D In Antiphospholipid Syndromesupporting
confidence: 88%
“…Seasonal variations in VitD concentrations were demonstrated in PAPS patients same as in healthy controls, with preserved differences in its level between these two groups through all seasons [88,90]. These differences were most pronounced during summer, while they were not statistically significant only during the spring.…”
Section: Role Of Vitamin D In Antiphospholipid Syndromementioning
confidence: 67%
See 1 more Smart Citation
“…In addition, in vitro NK cytotoxicity assays demonstrated significant suppression at an E:T ratio of 50:1 when treated with Vitamin D compared to the control group, demonstrating evidence that low Vitamin D may be associated with increased NK cell activity in women with recurrent pregnancy loss. Additionally, in a retrospective cohort study of 115 women with antiphospholipid syndrome (APS), median vitamin D levels in APS patients were significantly lower compared to healthy volunteers (n=128), although the authors report possible confounding factors related to provider recommendation of increased sunscreen use in the APS cohort [22]. Tavakoli et al [23] reported similar cytokine profiles and vitamin D expression of whole endometrial cells obtained from women with unexplained recurrent pregnancy loss (n=8) compared to age matched controls (n=8), although the authors do not address the limitations of the small sample size.…”
Section: Pregnancy Lossmentioning
confidence: 99%
“…Tra le donne in premenopausa con pAPS più del 50% dei casi presenta ipovitaminosi D [5][6][7]: livelli < 15 ng/ml risultano significativamente associati agli eventi trombotici [8].…”
unclassified